Mediating model of brand equity and its application - Umesh Ramchandra Raut; Prafulla Arjun Pawar; Pedro Quelhas Brito; Gyanendra Singh Sisodia (Spanish Journal of Marketing-ESIC, 2019)
Purpose – This paper aims to examine the mediating role of brand satisfaction and brand trust in brand equity antecedents and outcomes through an empirical investigation of brand equity elements. Design/methodology/approach – A survey was conducted in Pune and Mumbai, two prominent cities of India. A structured questionnaire focussed on garnering responses on measuring brand equity antecedents and outcomes was circulated to the cell phone users. The questionnaire aimed to assess the role of two additional variables, namely, brand satisfaction and brand trust, in the existing and the conceptual model of brand equity (Keller, 2001). Based on the data analysis, a structural equations path and the mediating model were developed. Findings – The findings of this study show that the new brand equity model is highly relevant in predicting brand equity as compared to the existing brand equity model (Keller, 2001). The brand equity mediation model clearly elucidates the role of brand trust and brand satisfaction. Research limitations/implications – With reference to a theoretical contribution, the study broadens the existing hypothetical model of brand equity. The findings of this research provide a strategic and analytical model for brand managers to build brand relationships among their consumers. Originality/value – The present study challenges the existing model of brand equity (Keller, 2001) and further makes an effort to fill in the gaps in the existing theoretical model of brand equity.